A transformative translational change programme to introduce genomics into healthcare: a complexity and implementation science study protocol. Issue 3 (5th March 2019) - Taylor, Natalie; Best, Stephanie; Martyn, Melissa; Long, Janet C; North, Kathryn N; Braithwaite, Jeffrey; Gaff, Clara
Abstract : Introduction: Translating scientific advances in genomic medicine into evidence-based clinical practice is challenging. Studying the natural translation of genomics into 'early-adopting' health system sectors is essential. We will (a) examine 29 health systems (Australian and Melbourne Genomics Health Alliance flagships) integrating genomics into practice and (b) combine this learning to co-design and test an evidence-based generalisable toolkit for translating genomics into healthcare. Methods and analysis: Twenty-nine flagships integrating genomics into clinical settings are studied as complex adaptive systems to understand emergent and self-organising behaviours among inter-related actors and processes. The Effectiveness–Implementation Hybrid approach is applied to gather information on the delivery and potential for real-world implementation. Stages '1' and '2a' (representing hybrid model 1) are the focus of this protocol. The Translation Science to Population Impact (TSci Impact) framework is used to study policy decisions and service provision, and the Theoretical Domains Framework (TDF) is used to understand individual level behavioural change; both frameworks are applied across stages 1 and 2a. Stage 1 synthesises interview data from 32 participants involved in developing the genomics clinical practice systems and approaches across five 'demonstration-phase' (early adopter) flagships. In stage 2a, stakeholders are providing quantitative and qualitative data on process mapping, clinical audits, uptake and sustainability (TSci Impact), and psychosocial and environmental determinants of change (TDF). Findings will be synthesised before codesigning an intervention toolkit to facilitate implementation of genomic testing. Study methods to simultaneously test the comparative effectiveness of genomic testing and the implementation toolkit (stage 2b), and the refined implementation toolkit while simply observing the genomics intervention (stage 3) are summarised. Ethics and dissemination: Ethical approval has been granted. The results will be disseminated in academic forums and used to refine interventions to translate genomics evidence into healthcare. Non-traditional academic dissemination methods (eg, change in guidelines or government policy) will also be employed.